'Crazy, mad, and dangerous' : a critical discourse analysis of the (re)construction of mental illness in South African magazines - Wilkinson, Laura Gery (Stellenbosch : Stellenbosch University, 2019)
Thesis (MA)--Stellenbosch University, 2019.